Antioxidant potential and content of phenolic compounds in ethanolic extracts of selected parts of Andrographis paniculata - Rafat, A.; Philip, K.; Muniandy, S. (Academic Journals, 2010)
The present study investigated the antioxidant capacity and total content of phenolic compounds in an ethanolic extract of leaves, stems and fruits of Andrographis paniculata, a medicinal plant. The antioxidant activity of the samples was evaluated by the red cell hemolysis assay, free radical scavenging and superoxide dismutase activities. The Folin-Ciocalteu reagent assay was used to estimate the phenolic content of extracts. Leaf extracts showed the highest antioxidant potential followed by stem and fruit extracts with the rabbit erythrocytes hemolysis and superoxide dismutase activity assays. However, A. paniculata fruit extracts exhibited the highest DPPH free radical scavenging activity compared to the other extracts. A positive correlation between free radical scavenging capacity and the content of phenolic compounds was found in the fruit, leaf and stem extracts of this plant.